2004
DOI: 10.1002/uog.1045
|View full text |Cite
|
Sign up to set email alerts
|

Reduced antioxidant capacity in second‐trimester pregnancies with pathological uterine perfusion

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
12
1
1
Order By: Relevance
“…Notably, an abnormal uterine perfusion characterizes pregnancies at risk for these pregnancy complications and precedes their clinical manifestation. However, only approximately one third of the pregnant women with abnormal uterine perfusion develop a complication, whereas the others have a normal course of pregnancy despite the high uteroplacental resistance (11).…”
Section: First Published Online March 28 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, an abnormal uterine perfusion characterizes pregnancies at risk for these pregnancy complications and precedes their clinical manifestation. However, only approximately one third of the pregnant women with abnormal uterine perfusion develop a complication, whereas the others have a normal course of pregnancy despite the high uteroplacental resistance (11).…”
Section: First Published Online March 28 2006mentioning
confidence: 99%
“…Independently other pregnant women with manifest pathology such as preeclampsia (18 patients) or isolated IUGR (nine patients) were recruited in the third trimester. The second-trimester Doppler investigations were performed using a LOGIQ 9 ultrasound machine (GE, Solingen, Germany) as described before (11). Preeclampsia was defined according to the guidelines of the International Society for the Study of Hypertension in Pregnancy (13).…”
Section: Experimental Subjectsmentioning
confidence: 99%
“…Oxidative stress by this criterion is present in women with abnormal Doppler velocimetry whether they subsequently have preeclampsia, FGR or normal pregnancy outcomes. [37]…”
Section: Pathophysiological Markers Of Placental Dysfunctionmentioning
confidence: 99%
“…Emerging evidence indicates that vascular functional and structural damage caused by yet to be identified mediators present in the maternal circulation of preeclampsia patients plays a causative role in the development of hypertension and proteinuria, two of the major symptoms in these patients [2]. In 1999, Wallukat et al [3] first reported that the autoimmune antibody against the second extracellular loop (165-191) of angiotensin II receptor type 1 (AT1-AA) is present in preeclamptic patients but not in healthy pregnancies or those with essential hypertension, and proposed that AT1-AA induces, similar to angiotensin II, an increase of the beating rate in spontaneously beating neonatal rat cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%